2017
DOI: 10.1136/bmjopen-2017-017974
|View full text |Cite
|
Sign up to set email alerts
|

Association of individual and neighbourhood socioeconomic status with physical activity and screen time in seventh-grade boys and girls in Berlin, Germany: a cross-sectional study

Abstract: ObjectivesFew studies have explored the impact of neighbourhood socioeconomic status (SES) on health behaviours in youths in Germany. Our aim was to investigate the association of individual and neighbourhood SES with physical activity (PA) and screen time (ST) in students aged 12–13 years in Berlin.DesignCross-sectional study.SettingSecondary schools (high schools and integrated secondary schools) in Berlin, Germany.ParticipantsA total of 2586 students aged 12–13 years (seventh grade).Main outcome measuresSoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 68 publications
2
17
1
Order By: Relevance
“…Slightly more knowledge exists of associations between social environment in the home setting and preschool children's screen time as an indicator of ST [21]; however, the correlates of screen time and overall ST seem to be distinct [22]. Another relevant aspect of social environment is socioeconomic status (SES) and its associations with children's behaviors [23]. Studies indicate associations between lower parental SES or lower neighborhood SES, and a higher risk of an unhealthier lifestyle and cardiovascular disease [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Slightly more knowledge exists of associations between social environment in the home setting and preschool children's screen time as an indicator of ST [21]; however, the correlates of screen time and overall ST seem to be distinct [22]. Another relevant aspect of social environment is socioeconomic status (SES) and its associations with children's behaviors [23]. Studies indicate associations between lower parental SES or lower neighborhood SES, and a higher risk of an unhealthier lifestyle and cardiovascular disease [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Data were collected at baseline, after 1 and 2 years during classes using self-report questionnaires that were developed on the basis of the standardised and validated questionnaires for adolescents, such as the ones used in the HBSC survey [34][35][36]. Details of the data assessment and a description of the variables were described previously [28,33].…”
Section: Data Collectionmentioning
confidence: 99%
“…What our study adds to these longitudinal data is the description of different trajectories for PA and ST. To our knowledge, this is the first German study investigating PA and ST trajectories and their predictors in school students. In addition to the longitudinal design, a novelty of our study is the size of the study sample and the location in a metropolitan area including a high percentage of students with migration background and different levels of socioeconomic status which have been shown to be representative of Berlin school students [28,50].…”
Section: Main Study Findings and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, low income-more educated levels put more strategies to restrict exposure to electronics (10). In 2017, Krist et al (11) studied the association of SES with physical activity and ST. They concluded that, low SES was associated with high ST. On the other hand, Jamali et al in 2017 (12) found that, children who belonged to low SES had significantly low ST. Socioeconomic status affects the availability of electronic screens at home, attitude toward electronic screens, media habits like the age when children begin to be exposed to media, the amount of exposure to electronic screens and type of watched materials (9).…”
Section: Introductionmentioning
confidence: 99%